2021
DOI: 10.1177/1971400920988665
|View full text |Cite
|
Sign up to set email alerts
|

Limited usefulness of routine head and neck CT angiogram in the imaging assessment of dizziness in the emergency department

Abstract: Objective To assess the usefulness of head and neck computed tomography angiogram for the investigation of isolated dizziness in the emergency department in detecting significant acute findings leading to a change in management in comparison to non-contrast computed tomography scan of the head. Methods Patients presenting with isolated dizziness in the emergency department investigated with non-contrast computed tomography and computed tomography angiogram over the span of 36 months were included. Findings on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 31 publications
2
19
0
1
Order By: Relevance
“…Our systematic review identified a single retrospective study of 153 patients with undifferentiated dizziness, in whom the attending physician decided (for unspecified reasons) to perform a head and neck CTA. The CTA showed findings in five patients but only two of them (2/153, 1.3%) had findings that were causing their dizziness 44 . Indirect evidence of CTA is consistent with this finding.…”
Section: Methodssupporting
confidence: 67%
“…Our systematic review identified a single retrospective study of 153 patients with undifferentiated dizziness, in whom the attending physician decided (for unspecified reasons) to perform a head and neck CTA. The CTA showed findings in five patients but only two of them (2/153, 1.3%) had findings that were causing their dizziness 44 . Indirect evidence of CTA is consistent with this finding.…”
Section: Methodssupporting
confidence: 67%
“…5,20,23 three studies evaluated the outcome of all central causes, with sensitivity ranging from 21.4% to 43.4% and specificity ranging from 90% to 100%. 19,21,22 Meta-analysis revealed a pooled sensitivity of 28.5% (95% CI 14.4%-48.5%), specificity of 98.9% (95% CI 93.4%-99.8%), positive likelihood ratio (LR) of 26.2 (95% CI 5.6-123.4), and negative LR of 0.72 (95% CI 0.58-0.91). When a subgroup of the four studies with a high risk of bias was analyzed, sensitivity estimates increased slightly to 38.8% (95% CI 25.6%-53.8%) without a significant change in specificity (Table 3).…”
Section: Ct Scanmentioning
confidence: 99%
“…Según Guarnizo et al (18), tanto la TAC sin contraste como la angiografía por tomografía computarizada (ATC) de la cabeza y el cuello tienen un bajo rendimiento diagnóstico para la detección de causas centrales de mareos. La TAC de cráneo simple presentó una sensibilidad del 21,4 % y una especificidad del 100 %; mientras que la ATC presentó una sensibilidad del 14,3 % y una especificidad del 97,7 % en la identificación de causas centrales de vértigo/mareo.…”
Section: Estudios De Neuroimagenunclassified